Addressing the Climate Change on Oral Health and Caries in Early Childhood - Sajid Ali Majeedano, Maham Shah, Farah Deeba Shaikh, Nourain Atif, Nighat Zia, Muhammad Amin Sahito, Rehmatullah Kandhro, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Dental caries is fundamentally a chronic health problem that may be prevented, but recent worldwide estimates indicate that oral health has not improved over the last 25 years. However, environmental change causes dry weather and high alkalinity in ground waters, which promotes fluoride release from mud and fluorite-bearing rocks. High temperatures cause ground waters to have prolonged home seasons, resulting in high fluoride levels in the water from water-rock interactions, even though fluorides in water are beneficial to tooth health and reduce the risk of caries in early childhood. Excessive fluoride exposure can cause severe fluorosis, which increases the risk of caries. Objective: Research aims to examine how climate change, water accessibility, and diet affect ECC. Methods: A descriptive cross-sectional study was conducted at different clinics of Hyderabad city in time frame of three months. Through purposive sampling, 100 children aged 1-5 years, both genders with dental caries, with parents’ permission, were included in the present study, whereas children with systemic diseases affecting the oral region were excluded. Data was collected in time period of three months by employing a purposive sampling technique. SPSS version 26.0 was used for data analysis. Chi-square test was applied with a significant level of p-value <0.05. Results: Children using tap water had significantly higher caries prevalence (43 cases) than those using bottled water (26 cases) (p < 0.0001). Water source type did not show a significant association with caries (p = 0.335). Similarly, changes in water availability (p = 0.47) and fluoride content awareness (p = 0.465) were not significantly associated with caries prevalence. However, climate change awareness was significantly associated with caries prevalence, with 66 cases among aware families compared to 3 cases among those unaware (p = 0.011) Conclusion: The present research showed the complexity of the background of early childhood caries and identified numerous environmental factors, oral hygiene practices, and parents’ roles in this process. Keywords: Caries, Childhood, Climate Change, Oral Health